Recent results on top quark mass and properties and rare/anomalous top quarks interactions in CMS - Sebastian Wuchterl (SciPost Physics Proceedings, 2022)
The amount of data collected by the CMS experiment at the CERN LHC in the second data taking period provides the possibility to study absolute and differential cross sections of top quark interaction processes with high precision. Utilizing these results, fundamental standard model parameters such as the top quark mass are extracted. Moreover, given standard model measurements are interpreted in the context of Beyond the standard model theories. Recent results on top quark properties and rare or anomalous top quark interactions by CMS are presented in these proceedings. Furthermore, the implications of experimental results to effective field theory are discussed.